MicroRNA‐33 and SIRT1 influence the coronary thrombus burden in hyperglycemic STEMI patients. Issue 2 (11th July 2019) - D'Onofrio, Nunzia; Sardu, Celestino; Paolisso, Pasquale; Minicucci, Fabio; Gragnano, Felice; Ferraraccio, Franca; Panarese, Iacopo; Scisciola, Lucia; Mauro, Ciro; Rizzo, Maria Rosaria; Mansueto, Gelsomina; Varavallo, Federica; et al.
Abstract: Primary percutaneous coronary intervention (PPCI) is a pivotal treatment in ST‐segment elevation myocardial infarction (STEMI) patients. However, in hyperglycemic‐STEMI patients, the incidence of death is still significant. Here, the involvement of sirtuin 1 (SIRT1) and miR33 on the pro‐inflammatory/pro‐coagulable state of the coronary thrombus was investigated. Moreover, 1‐year outcomes in hyperglycemic STEMI in patients subjected to thrombus aspiration before PPCI were evaluated. Results showed that hyperglycemic thrombi displayed higher size and increased miR33, reactive oxygen species, and pro‐inflammatory/pro‐coagulable markers. Conversely, the hyperglycemic thrombi showed a lower endothelial SIRT1 expression. Moreover, in vitro experiments on endothelial cells showed a causal effect of SIRT1 modulation on the pro‐inflammatory/pro‐coagulative state via hyperglycemia‐induced miR33 expression. Finally, SIRT1 expression negatively correlated with STEMI outcomes. These observations demonstrate the involvement of the miR33/SIRT1 pathway in the increased pro‐inflammatory and pro‐coagulable state of coronary thrombi in hyperglycemic STEMI patients. Abstract : Upregulation of miR33 and downregulation of SIRT1 protein in hyperglycemic coronary thrombi contribute to pro‐inflammatory/pro‐coagulability in STEMI patients. These findings open a new perspective in the setting of therapeutic strategies to improve clinical outcomes in hyperglycemic patients with STEMI.